OPTIMIZATION OF THE QUEU SYSTEM USING LINE BALANCING METHODS AND FLEXSIM SOFTWARE SIMULATION AT THE SIAGA MEDIKA BANYUMAS HOSPITAL - Karunianto, Hernawan; Agusti, Febrina; Buwono, Ringgo Ismoyo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Service is an important aspect for the service industry, including hospitals, one of the important aspects in a service is the queue. Siaga Medika Banyumas Hospital provides services with 3 doctors and there are 4 main services at Siaga Medika Banyumas Hospital, namely, registration, doctor services, payment and taking medicine. This research carries out queue simulations using flexsim and line balancing calculations. The results show that the line balancing calculation in the initial state has an average path efficiency of 64.90% with simulation results of 31 patients queuing. calculations after line balancing showed an average path efficiency of 87.17% with simulation results of 37 patients queuing. The alternative of adding 1 new doctor obtained an average path efficiency of 78.80% and made a difference in the number of queues for doctor services to 14 patients.